Dopamine in Auditory Nuclei and Lemniscal Projections is Poised to Influence Acoustic Integration in the Inferior Colliculus - Harris, Sharonda; Afram, Renee; Shimano, Takashi; Fyk-Kolodziej, Bozena; Walker, Paul D.; Braun, Rod D.; Holt, Avril Genene (Frontiers in Neural Circuits, 2021)
Abstract Dopamine modulates the activity of nuclei within the ascending and descending auditory pathway. Previous studies have identified neurons and fibers in the inferior colliculus which are positively labeled for tyrosine hydroxylase, a key enzyme in the synthesis of dopamine. However, the origins of the tyrosine hydroxylase positive projections to the inferior colliculus have not been fully explored. The lateral lemniscus provides a robust inhibitory projection to the inferior colliculus and plays a role in temporal processing of sound. In the present study, immunoreactivity for tyrosine hydroxylase was examined in animals with and without 6-hydroxydopamine (6-OHDA) lesions. Lesioning, with 6-OHDA placed in the inferior colliculus, led to a significant reduction in tyrosine hydroxylase immuno-positive labeling in the lateral lemniscus and inferior colliculus. Immunolabeling for dopamine beta-hydroxylase and phenylethanolamine N-methyltransferase, enzymes responsible for the synthesis of norepinephrine and epinephrine, respectively, were evaluated. Very little immunoreactivity for dopamine beta-hydroxylase and no immunoreactivity for phenylethanolamine N-methyltransferase was found within the cell bodies of the dorsal, intermediate or ventral nucleus of the lateral lemniscus. The results indicate that catecholaminergic neurons of the lateral lemniscus are likely dopaminergic and not noradrenergic or adrenergic. Next, high pressure liquid chromatography analysis was used to confirm that dopamine is present in the inferior colliculus and nuclei that send projections to the inferior colliculus, including the cochlear nucleus, superior olivary complex, lateral lemniscus, and auditory cortex. Finally, fluorogold, a retrograde tracer, was injected into the inferior colliculus of adult rats. Each subdivision of the lateral lemniscus contained fluorogold within the somata, with the dorsal nucleus of the lateral lemniscus showing the most robust projections to the inferior colliculus. Fluorogold-tyrosine hydroxylase colocalization within the lateral lemniscus was assessed. The dorsal and intermediate nuclei neurons exhibiting similar degrees of colocalization, while neurons of the ventral nucleus had significantly fewer colocalized fluorogold-tyrosine hydroxylase labeled neurons. These results suggest that several auditory nuclei that project to the inferior colliculus contain dopamine, dopaminergic neurons in the lateral lemniscus project to the inferior colliculus, and that dopaminergic neurotransmission is poised to play a pivotal role in the function of the inferior colliculus.